Assessing cognitive dissonance and self-worth: investigating the influence of fast fashion following and social media addiction among young adults in Bangladesh - Keya , Ummay Kulsum; Bakul, Fariea (Dhaka University Journal of Biological Sciences, 2025)
In today’s digitalized modern society people are getting affected by the practice of fast fashion buying and become the victims of post purchase indecisions and social media addictions. Understanding how young adults’ cognitive dissonance and sense of self-worth are related to fast fashion was one of the main goals of the current study. The present study also investigated whether any other factors, such as gender, social media addiction in terms of online shopping, educational background, and income, might have an impact on the study’s results. Women who purchase fast fashion are more likely than males to experience cognitive dissonance when making a purchase, according to the present study results. Fast fashion and cognitive dissonance following purchase are discovered to have a positive relationship. Regression analysis determined that fast fashion and social media can predict cognitive dissonance after making a purchase as well as three sources of self-worth: appearance, God’s love, and virtue. The results of the current study show a relationship between social media use and how it affects customer behaviour in the fast-fashion clothing sector, which may cause cognitive dissonance. Furthermore, there is evidence that social media use and rapid fashion have a negative impact on academic achievement, psychological health, and self-worth. Interestingly, the study shows that under this situation, women are more likely than males to experience cognitive dissonance. In conclusion, fast fashion plays a much greater role in our lives than we realize in terms of affecting our self-worth and cognitive dissonance and using of social media to for purchase purposes. Dhaka Univ. J. Biol. Sci. 34(1): 145-153, 2025 (January)